Pengaruh Iklan Layanan Spotify Premium Terhadap Minat Berlangganan Konsumen - Muhammad Fikri Maulana; Muhammad Aqshel Revinzky; Andry Mochmad Ramdan (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2022)
The streaming audio application Spotify often inserts advertisements for users who do not subscribe to a premium subscription to the application. Advertising is needed by the company as a marketing strategy to influence consumer buying interest in order to increase profits for the company. Relying on quantitative methods with the Spearman Rank correlation test analysis technique. Researchers reveal the effect of Spotify Premium advertising on Digital Natives' interest in Bandung in buying premium features. The researcher collected samples using purposive sampling in the survey and determined the number of samples using Isaac and Michael's tables. The theory of A-T-R as an indicator of the independent variable and the AISAS model as an indicator of the dependent variable. The results of the study reveal that there is an influence between attractiveness variables such as awareness, trial, and reinforcement, on the buying interest variable seen from the significant and unidirectional correlation between variable X and Variable Y. Spotify premium service advertisements have been designed in such a way as to build a feeling of Awareness. Trial, and Reinforcement consumers, so as to trigger consumer buying interest. Research has strengthened the claim that audiences can be influenced by advertising.